Mangrove attribute preferences for environmental conservation: evident from choice modeling approach - Ibrahim, W.N.W; Mohd, F.; Alipiah, R.M.; Wan Anisah, E.; Suraya, I. (2019)
Mangrove forest provides a variety of service both ecologically and economically. But they are experiencing severe threats, with high annualized shrinkage rates in almost all countries. This situation emphasizes the decision maker to make efficient decision making on continuous sustainability of conservation programs by understanding the local community preferences of the mangrove attribute. To obtain this objective, this paper applies the choice modeling (CM) experiment method, which is the one of the preferred non-market valuation technique. CM is creating strong interest among researchers because of very flexible in dealing with complex models of "trade-offs" between attributes, so that makes it possible to model the community choices on selected mangrove attribute. To perform this technique, a series of choice card were distributed to 526 respondents from three areas around Setiu Wetlands (SW), Terengganu, Malaysia using face to face survey method. The result from multinomial logit model showed that the six attribute selected for the environmental conservation was significantly influenced community preferences. The results of this study indicate that the forest mangrove area (MANREA), water quality (WATERQ) and the price of mangrove sapling tree (PRICE) have the expected sign with higher marginality value for concerted efforts for sustainable management of the mangrove forest. The finding indicates that local communities are likely to support mangrove conservation management initiatives that promote sustainable use of the mangrove resources.